La Decision Financiere et Son Impact Sur la Performance Financiere Mesuree par la Rentabilite Cas de L'entreprise Nationale de Promotion Immobiliere .Enpi. Epe du Secteur de L'habitat - Tari, Mohamed Larbi; Attari, Abdennasser (جامعة محمد خيضر بسكرة - كلية العلوم الاقتصادية والتجارية وعلوم التسيير, 2018)
The effects of the financial structure on the performance of the Algerian public company operating in the housing sector in the context of the theory of hierarchical financing. They suggest in particular that the choice of a financing method, whether internal or external, debt or equity, long term or short term is likely to have different effects on financial performance. It is still necessary that the performance measure be defined and that the effects of these modes of financing converge whatever the chosen performance indicator. The long-term debt is positively correlated with the financial performance of the company, the debt runs short. In the end, self-financing also has a negative effect on the company's performance.
Keywords: السياسة المالية -- النظام المالي -- الاداء المالي -- القوائم المالية -- الشركة الوطنية للتطوير العقاري -- الجزائر -- المجتمع الجزائري